Assessment of sodium fluoroacetate (1080) in baits and its biodegradation by microorganisms - Kirkpatrick, Winifred E. (Curtin University, 1999)
In Western Australia dried meat baits containing 1080 are used extensively by agricultural and conservation organisations to control foxes and dingoes for the protection of agricultural production and native fauna. Field trials were conducted to assess 1080 loss from dried meat baits and this required the analysis of over five hundred baits. Because of this large number of baits it was essential to have a simple and efficient 1080 extraction procedure and method of 1080 analysis. In this study three methods of 1080 extraction and the new bioassay method for 1080 analysis were investigated. A simple and cost-effective 1080 extraction method using water with a 98% 1080 recovery rate was developed and modifications to the bioassay method were made.Factory-produced 1080 dried meat baits were laid in the field during different seasons at four locations in Western Australia, samples were collected over time and analysed for 1080 content using the bioassay. Rainfall was recorded and temperature data was collected for each site. Baits were exposed to the elements but were placed in mesh or wire cages to restrict invertebrate attack and prevent removal by vertebrates. Some baits were placed on the surface and others were buried. Initially 1080 loss from baits from all 4 sites was minimal, ranging from 0 - 21% at day 7 - 9. Further loss was gradual even when rainfall was recorded. Generally baits had to be exposed to at least 50 mm of rain before 1080 loss increased to 50%. At some sites baits continued to remain toxic to foxes even after long exposure. The mean 1080 content of baits from the Carnarvon site at day 226 was 2.0 mg (55% of the mean 1080 content of baits at day zero) with 137 mm of rainfall recorded for that period. Loss of 1080 from baits buried occurred at a faster rate than from baits placed on the surface during the same time period. By day 14 no 1080 was detected in the buried baits compared to the 68% detected in the surface baits. Under certain conditions 1080 loss from baits was minimal. Levels of 1080 in baits from Nangeen Hill remained fairly constant during the months of September to December 1995, and again during February to April 1996.Gastrolobium plant tissue and soil samples from the southwest of Western Australia were investigated for the presence of 1080 degrading microorganisms. Microbes were isolated and individually tested in solution containing 1080 as the sole carbon source. Isolates which showed 1080 degrading ability were further tested for their degrading efficiency in McClung carbon-free solution with added 1080 as the sole source of carbon and in factory 1080 waste solution, at 1080 concentrations of 20 and 200 mM. The effect of temperature on their rate of degradation was also examined. Thirteen isolates (7 fungi and 6 bacteria) showing varying degrees of 1080 degrading ability were obtained. Rates of 1080 degradation varied among isolates but were highest in the factory waste solution at the 20 mM concentration and in the McClung solution, where 1080 was the sole source of carbon, at the higher concentration of 200 mM. The most efficient isolates OSK and 10H (both Pseudomonas species) degraded all the 1080 present in sterile factory waste solution up to 20 mM 1080 concentration in 4 days and the isolate 1AF (Fusarium oxysporum) degraded 93% of 200 mM 1080 in the McClung solution in 9 days. The optimum temperatures for 1080 degradation were 30 degrees celsius and fluctuating ambient temperatures of 15 28 degrees celsius.